Quartz crystal microbalance studies of the contact between soft, viscoelastic solids - Kunze, Miriam (Langmuir : the ACS journal of surfaces and colloids, 2006)
Mechanical contact between a viscoelastic lens and a viscoelastic film has been probed by means of a quartz crystal microbalance operated in the impedance analysis mode. The frequency shift induced by the formation of the contact decreases with increasing film thickness because of the finite penetration depth of the acoustic shear wave. The dependence of frequency and bandwidth on film thickness and contact area is described within a sheet-contact model, which can be employed to quantitatively analyze mechanical contact in a wide range of materials problems. The model was tested by bringing a quartz crystal coated with an elastomeric gel into contact with a hemispherical cap of a similar gel. Both gels consisted of the thermoreversible gel Kraton G swollen in mineral oil. The experiments support the model well